Variety Evaluation, Release and Registration - Eastern and Central Africa Programme for Policy Analysis (ECAPAPA/ASARECA, 2003)
The harmonization of seed policies and regulation in the ASARECA member countries is the first step toward creating a seed market that is large enough to attract investment by local and international investors...